Intergovernmental transfers and revenue sharing in Spain - Santiago Alvarez-García; Javier Salinas-Jiménez; David Cantarero (European Regional Science Association (ERSA), 2004)
The main objective of this paper is to provide a general analysis of the evolution of the funding models of the Spanish Autonomous Communities (regional level) during the last decade and explore the main achievements of the new model (2001). In particular, the funding models that have been applied during these years are assessed comparing their results with the proponsed objectives that they tried to meet. Finally, special attention is paid to the developments achieved by the new model with respect to the previous one in terms of economic sufficiency (static and dynamic), joint responsibility for taxation and interregional solidarity measures. Key words: Federalismo Fiscal, Spanish Autonomous Communities, Economic Sufficiency, Fiscal Corresponsability, Interregional Solidarity. JEL classification: H7, H72, H77
Keywords: H7; H72; H77; 330; Federalismo Fiscal; Spanish Autonomous Communities; Economic Sufficiency; Fiscal Corresponsability; Interregional Solidarity